From social movement to economic movement: A historical study of the journey of the mbako batik industry in Temanggung (2009-2021) - Amalia, Husna; Setyaningsiih, Wahyu (Islah: Journal of Islamic Literature and History, 2024)
The purpose of this study is to analyze the protest of the Temanggung community against the 2009 fatwa on the haram of cigarettes; explain the process of establishing the Mbako Batik Industry as a protest action of the Temanggung community; and analyze the influence of the Mbako Batik Industry on the socio-economic life of the people of Tegaltemu Manding Temanggung Hamlet in 2013-2021. This thesis research uses a historical research method. The steps in the historical research method are: (1) Search and collection of data or heuristic, (2) Source criticism or verification, (3) Interpretation or interpretation, and (4) Historical writing or historiography. The primary source in this thesis is data from the Mbako Batik Company and interviews with the owners and batik makers of Batik Mbako. The results of this research include the following: The history of the Mbako Batik industry stands at the same time as the demonstration about rejecting the haram fatwa on cigarettes issued by the MUI. In addition, at the same time in 2009, many Temanggung tobacco farmers were worried that Temanggung tobacco farmers were threatened. Alm. Iman Nugroho established the batik industry and originated the name Batik Mbako by using the beauty of tobacco leaves as motifs and everything related to tobacco plants. The development of Batik Mbako started from the beginning of its establishment, only the home industry turned into a company that has two places, namely the Batik Mbako Workshop as a place for batik production and the Batik Mbako Showroom which is used as a store selling Batik Mbako. The influence of Batik Mbako on the socio-economic condition of the community in Tegaltemu Hamlet can be seen from several levels, namely the increased level of education, the opening of jobs, and the absorption of labor, namely as Batik Mbako batik. Then the increase in income, if viewed from most of the income obtained by the community, the batik makers with the salary they get can help meet their daily needs, support the family economy, and of course get a more decent and prosperous life and get a better quality of life.